FOXP3+Helios+ Regulatory T Cells, Immune Activation, and Advancing Disease in HIV-Infected Children. (15th August 2016) - Khaitan, Alka; Kravietz, Adam; Mwamzuka, Mussa; Marshed, Fatma; Ilmet, Tiina; Said, Swalehe; Ahmed, Aabid; Borkowsky, William; Unutmaz, Derya
Abstract : Abstract: Regulatory T cells (Tregs) are functionally suppressive CD4 T cells, critical for establishing peripheral tolerance and controlling inflammatory responses. Previous reports of Tregs during chronic HIV disease have conflicting results with higher or lower levels compared with controls. Identifying true Tregs with suppressive activity proves challenging during HIV infection, as traditional Treg markers, CD25 and FOXP3, may transiently upregulate expression as a result of immune activation (IA). Helios is an Ikaros family transcription factor that marks natural Tregs with suppressive activity and does not upregulate expression after activation. Coexpression of FOXP3 and Helios has been suggested as a highly specific marker of "bona fide" Tregs. We evaluated Treg subsets by FOXP3 coexpressed with either CD25 or Helios and their association with HIV disease progression in perinatally infected HIV-positive children. Identifying Tregs by FOXP3 coexpression with Helios rather than CD25 revealed markedly higher Treg frequencies, particularly in HIV+ children. Regardless of antiretroviral therapy, HIV-infected children had a selective expansion of memory FOXP3+Helios+ Tregs. The rise in memory Tregs correlated with declining HIV clinical status, indicated by falling CD4 percentages and CD4:CD8 ratios and increasing HIV plasma viremia and IA. In addition, untreated HIV+ children exhibited an imbalance between the levels of Tregs and activated T cells. Finally, memory Tregs expressed IA markers CD38 and Ki67 and exhaustion marker, PD-1, that tightly correlated with a similar phenotype in memory CD4 T cells. Overall, HIV-infected children had significant disruptions of memory Tregs that associated with advancing HIV disease. Abstract : Supplemental Digital Content is Available in the Text.